Analytical Elastic Modeling of Rail and Fastener Longitudinal Response. Issue 5 (May 2021) - Trizotto, Matheus; Dersch, Marcus S.; Edwards, J. Riley; Lima, Arthur
The rail fastening system plays a critical role in maintaining proper railroad track geometry by transferring vertical, lateral, and longitudinal forces from the rails to crossties. Broken spikes in elastic fastening systems have been linked to inadequate transfer of longitudinal loads, posing a safety risk for timber crosstie ballasted track. Longitudinal track demand caused by passing trains has been investigated in previous research, but the magnitude and distribution of longitudinal fastener loads is not well understood or documented. To address these track component failures and improve fastener design, this paper presents a validated analytical model that estimates longitudinal rail seat loads, advancing current formulations to focus specifically on the rail seat. The validated method was used to quantify the distribution and magnitude of longitudinal loads in both the rail and fastening system caused by passing trains. Further, this paper quantifies the effect of track stiffness, number of powered locomotives, and wheel spacing on these distributions and magnitudes. This information provides valuable insight into the specific type of spike failures that have led to at least ten derailments and the requirement of manual walking inspections on multiple North American heavy axle load railroads as detailed in this paper. Further, this method can be used to quantify the longitudinal fastener loads for different track conditions to advance the mechanistic-empirical track design philosophy for elastic fastening systems.